2022
DOI: 10.1038/s41580-022-00456-z
|View full text |Cite
|
Sign up to set email alerts
|

Defining roles of specific reactive oxygen species (ROS) in cell biology and physiology

Abstract: Reactive oxygen species (ROS) is a generic term that defines a wide variety of oxidant molecules with vastly different properties and biological functions that range from signalling to causing pathological damage. Consequently, the molecular description of oxidants needs to be chemically precise for rational translation of research on their biological effects into therapeutic benefit in redox medicine. This Expert Recommendation article pinpoints key issues associated with identifying and explaining the physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
572
0
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 844 publications
(596 citation statements)
references
References 275 publications
4
572
0
20
Order By: Relevance
“…Paired cell cultures were maintained under 18 kPa O 2 or adapted to 5 kPa O 2 for 5 days in our O 2 -regulated workstations. We have previously demonstrated that cells are able to alter their redox phenotype dependent on the ambient O 2 level [ [31] , [32] , [33] , [34] ].…”
Section: Methodsmentioning
confidence: 99%
“…Paired cell cultures were maintained under 18 kPa O 2 or adapted to 5 kPa O 2 for 5 days in our O 2 -regulated workstations. We have previously demonstrated that cells are able to alter their redox phenotype dependent on the ambient O 2 level [ [31] , [32] , [33] , [34] ].…”
Section: Methodsmentioning
confidence: 99%
“…Critically, our study raises an important caveat about interpreting biochemical activation and functionality of metal-containing enzymes in cells cultured under standard room air conditions. Given the caveats concerning chemical uorescence probes 50 , further advances in novel genetic biosensors for high-resolution, real-time imaging of labile iron levels are warranted to enhance our understanding of iron-dependent metabolism and signaling pathways in cells under wellde ned physiological oxygen levels 51 .…”
Section: Discussionmentioning
confidence: 99%
“…We noted that NOX4, under HO, augmented mt ROS production leading to epithelial cell apoptosis. ROS outlines diverse oxidant molecules possessing distinctive biological functions and properties and biological functions ( Sies et al, 2022 ). We focused on H 2 O 2 and O 2 .- .…”
Section: Discussionmentioning
confidence: 99%